Feresa attenuata Gray 1874 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Feresa attenuata Gray 1874 Feresa attenuata Gray 1874, Ann. Mag. Nat. Hist., ser. 4, 14: 238-239. Type Locality: "South Seas.". Vernacular Names: Pygmy Killer Whale. Synonyms: Feresa intermedius (Gray 1827); Feresa intermedius (Gray 1843); Feresa intermedia (Gray 1846); Feresa occulta Jones and Packard 1956. Distribution: Worldwide: tropical to warm-temperate waters. Conservation: CITES – Appendix II; IUCN – Data Deficient. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Cetacea, pp. 723-743 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 728, DOI: 10.5281/zenodo.7316519